Evaluasi dan Analisis UI/UX Website Teak Tree Eatery & Living Menggunakan Metode UCD - Nugroho, Dhanang Satria; Nugroho, Adi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
A website has a significant role in this modern era, especially in distributing information to the public. An appealing website interface can make a someone interested in finding more information they are looking for. Moreover, a business will benefit significantly from the existence of a website. Teak Tree Eatery & Living is a business that specializes in F&B and Furniture which is located in Salatiga. Creating a UI/UX design for Teak Tree Eatery & Living uses the User-Centered Design method. This research aims to increase the website visitors' engagement so they decide to visit the location. The result of this research has a SUS value of 78,3, which is included in the B+ score category and GOOD for an adjective result so Users can accept the design. The answers were collected from 34 respondents.